Analysis of Risk Factors for Carpal Tunnel Syndrome (CTS) - Savitri, Kania Aviandi (Sriwijaya Journal of Neurology, 2024)
Introduction: Carpal tunnel syndrome (CTS) is one of the musculoskeletal disorders most frequently reported in hospitals. Research on risk factors for CTS in Indonesia is still limited. Therefore, this study aims to analyze the risk factors for CTS at Dharma Husada Hospital, Probolinggo, Indonesia. It is hoped that this research can provide more complete information about the risk factors for CTS in Indonesia. Methods: This study is an analytical observational research with a cross-sectional. This study uses secondary data obtained from the medical records installation at Dharma Husada Hospital, Probolinggo, Indonesia. Results: A total of 300 research subjects took part in this study. Female gender, age ≥50 years, work with repeated use of hands and wrists and length of work with wrists more than 6 hours per day are risk factors that play a major role in the incidence of CTS at Dharma Husada Hospital Probolinggo Indonesia. Conclusion: Jobs that require repetitive use of the hands and wrists are one of the main risk factors for CTS. This is caused by repeated pressure on the median nerve in the carpal tunnel.